African Red Slip Ware from Augusta Vindelicum/Augsburg (Raetia): Range of forms and chemical analyses - Heimerl, Ferdinand (Rei Cretariae Romanae Fautorum Acta, 2017)
This paper presents some results of a recent study on African Red Slip Ware (ARS), cooking ware and lamps from Augusta Vindelicum/Augsburg. In contrast to most Raetian sites, the provincial capital Augsburg offers a significant amount of North African pottery from the late 1st to the first half of the 5th century AD. That data allows for more in-depth analysis of the trade and settlement history of Augusta Vindelicum. The assemblage also serves as a meaningful reference for the pottery supply of Raetia. This article concentrates on the range and origin of North African pottery from Augsburg as well as on chemical analyses with wavelength-dispersive X-ray fluorescence (WD-XRF). Furthermore, distribution patterns of African Red Slip Ware in Raetia will be discussed.